Performance optimization solutions for NFV data plane - Yukai HUANG; Jinkun GENG; Ruilin LING; Dan LI (Dianxin kexue)
In recent years,network function virtualization (NFV) is arousing concern widely from both academia and industry due to its flexible deployment and low cost.However,the performance bottleneck becomes increasingly distinctive and hinders the progress of NFV technology.The major factors were studied which could seriously affect the performance of NFV data plane.Firstly,an analysis was conducted on the causes for various kinds of performance overheads.Then,the optimization solutions were summarized to mitigate these overheads.Finally,a brief introduction was made on two types of architecture,which could significantly improve the performance of NFV data plane.